Cardiac magnetic resonance imaging in repaired tetralogy of Fallot: A longitudinal midterm follow-up study. - Golnaz Houshmand; Rahem Rahmati; Elahe Meftah; Fatemeh Zarimeidani; Mohammadrafi Khorgami; Seyyed Mojtaba Ghorashi; Amir Fazeli; Negar Omidi; Sedigheh Saedi; Marzieh Motevalli; Majid Maleki; Hamidreza Pouraliakbar (PLoS ONE)
Background Biventricular dysfunction is frequent in patients with repaired tetralogy of Fallot, necessitating routine imaging to monitor for worsening conditions and determine whether procedures like pulmonary valve replacement (PVR) are needed. This study aimed to highlight the parameters of cardiac magnetic resonance imaging (CMR) and their association with adverse outcomes in the midterm follow-up of these patients. Methods This longitudinal study recruited all patients with a history of tetralogy of Fallot total correction (TFTC) who had two CMR images at a minimum three-month interval at Rajaie Center from 2007 through 2017. Results Fifty-six patients at a mean age of 15.23 ± 11.66 years at TFTC and a 1:1 gender distribution were assessed. Regarding adverse events, PVR was done on 18 patients (32%). Right and left ventricular dysfunction occurred in 43 (76.8%) and 18 (32.1%) patients, respectively. Death did not occur in the present study. RVOT fibrosis was present in 47 (92.2%). The stroke volume of both ventricles increased during the follow-up (P <0.05), although end-diastolic volume indices, end-systolic volume indices, ejection fractions, strain parameters, and ventriculoarterial coupling did not change significantly. Patients requiring PVR had a significantly higher end-systolic volume index in both ventricles (P <0.05) and a lower right-sided ejection fraction (P <0.01) and coupling ratio (P <0.05). The ejection fraction in the left ventricle correlated with global circumferential strain (P <0.01), while in the right ventricle, it correlated with global longitudinal strain (P <0.05) and the right-sided coupling ratio (P <0.01). Conclusion Myocardial strain and ventriculoarterial coupling parameters could underscore personalized-approached therapy and follow-up to improve outcomes.